Laboratory-Generated Autologous Skin Substitutes for Burn Treatment in Europe: Narrative Review, Experts’ Opinion, and Legal Considerations - Celine Auxenfans; Rocio G. Valencia; Philippe Abdel-Sayed; Miguel Alaminos; Jean-François Brunet; Fernando Campos; Jesus Chato-Astrain; Gloria Carmona; Anthony de Buys Roessingh; Stephanie Droz-Georget; Melinda Farkas; Ana Fernandez Gonzalez; et al. (European Burn Journal)
Autologous skin substitutes represent a promising advancement in the treatment of burn injuries, offering personalized solutions for patients with extensive skin loss. This white paper synthesizes the current knowledge on laboratory-generated autologous skin substitutes in Europe, incorporating expert opinions and legal considerations. The white paper examines the scientific principles underlying autologous skin substitute development, including cell sourcing, bioengineering techniques, and clinical applications. The regulatory framework governing the production and use of these advanced therapies in Europe is also examined, highlighting challenges in standardization, safety, and approval pathways. The text features expert insights that offer a real-world perspective on the clinical viability and translational hurdles of autologous skin substitutes. The findings highlight the potential of autologous skin substitutes to improve burn treatment outcomes while emphasizing the need for harmonized regulations to facilitate clinical implementation. Despite technological advancements, significant challenges persist, including production costs, scalability, and long-term efficacy. Another focus of this white paper are the legal changes, which have significantly impacted the production and availability of these technologies. The review concludes that while autologous skin substitutes hold great promise, further research, regulatory refinement, and interdisciplinary collaboration are essential to optimize their integration into clinical practice.